Augmenting Internet-Based Cognitive Behavioral Therapy for Major Depressive Disorder With Transcranial Infrared Laser Stimulation - Douglas W. Barrett; Christopher G. Beevers; F. Gonzalez-Lima (Biological Psychiatry Global Open Science)
Background: Transcranial infrared laser stimulation (TILS) is a noninvasive form of photobiomodulation that facilitates prefrontal energy metabolism and oxygenation, resulting in cognitive-enhancing effects. Cognitive behavioral therapy is a mainstream treatment for major depressive disorder. This is the first study to investigate whether TILS would augment the antidepressant effects of internet-based cognitive behavioral therapy. Methods: Sixty participants with major depressive disorder were given access to Deprexis, a form of internet-based cognitive behavioral therapy, for 12 weeks. After the first 2 weeks, the 40 participants who had improved at least 10% in depressive symptoms from baseline as measured by the Quick Inventory of Depressive Symptomatology–Self-Report were randomly assigned to Deprexis in combination with TILS or sham/placebo. There were no significant group differences in demographics or initial depression data. Results: There was a 43% reduction in Quick Inventory of Depressive Symptomatology–Self-Report scores in the sham group from the initial score to the week 12 score, while adding TILS as an adjunct therapy resulted in a reduction of 56%. Therefore, TILS resulted in an additional 30% reduction in Quick Inventory of Depressive Symptomatology–Self-Report scores ([56−43]/43 = 30%). Participants who received TILS to the right forehead once a week for 4 weeks showed a significantly greater reduction of depressive symptoms than participants who received sham/placebo. Participants reported no adverse effects. Conclusions: While Deprexis alone significantly reduced depression scores in the placebo control group, this beneficial effect was augmented with the addition of TILS as an adjunct therapy. Additional research that pairs neuroenhancement methods such as TILS with cognitive interventions may reveal the potential to improve treatment outcomes in depression and other psychiatric disorders.